The impact of inflammation on Resistin, IL-6 and CRP in Acute Myocardial Infarction Patients. - Ibrahim, Ammal E.; EL-Yassin, Hadef D.; Sachit AL-Janabi, Hamid K. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Inflammation contributes across the spectrum of cardiovascular disease, including the earliest steps in atherogenesis. Myocardial Infarction (MI) is most commonly due to occlusion (blockage) of a coronary artery following the rupture of a vulnerable atherosclerotic plaque. It has been suggested that the adipose tissue may play an important role in mediating this chronic inflammatory process, human resistin, is a 12.5-kDa protein, it found in the inflammatory zone. Interleukin-6 (IL-6) is a pro-inflammatory cytokine, it secreted by T cells and macrophages to stimulate immune response. C-reactive protein (CRP) is a protein found in the blood, the levels of CRP rise in response to inflammation. Objective: to determine the role of Resistin in Acute myocardial infarction patients and its effects on IL-6 and CRP. Patients and Methods: The study included 50 patients with Acute Myocardial Infarction and 40 healthy subject as control, levels of resistin, Interleukin-6 (IL-6) and CRP were measured. Results: The levels of resistin, IL-6 and CRP were significantly elevated with (p<0.001). There was positive correlation between resistin with IL-6 and CRP in acute myocardial infarction patients. Conclusions: There was significantly increasing in levels of resistin, in acute myocardial infarction patients and this increasing may be related to inflammation. Resistin positively correlated with proinflammatory factor (IL-6 and CRP) so it have inflammation properties may consider a cardiovascular risk factor.